THE CONFLICTS IN THE DRAMA SCRIPT LOVE BEFORE BRAINZ ADAPTED FROM THE NOVEL ENTITLED WARM BODIES BY ISAAC MARION AS MATERIAL FOR TEACHING DRAMA CLASS - Anugrah Cahyo Hudi (Universitas PGRI Semarang, 2014)
The main purposes of the final project are finding out the conflicts happen in the drama script “Love before Brainz” adapted from the novel entitled Warm Bodies by Isaac Marion as material for teaching drama class, finding out the most dominant conflicts in the drama script and discusses the contributions of the final project in English language teaching. Library research is used in this final project. Library research points out not on the result, but on the process. The writer deals with some books that are available in the library. The information is obtained by reading books, searching internet and other references related to the subject matter. To analyze the conflicts in the drama script “Love before Brainz”, the writer reads the play script in order to understand the content of it many times. After analyzing the conflicts in the drama script, the writer finds the most dominant conflicts and the contributions of this study in English language teaching. From this drama script, the writer knows that the most dominant conflicts is man versus man. Because the conflicts happen between R (zombie) with Julie, Julie with her father (colonel Grigio), and R with Julie’s father